Analisis Wacana Bahasa Berita Kriminal Pembunuhan pada Berita Daring Kompas.com - Nurmaulidia Nurmaulidia; Majidatun Nuraini; Ryanitha Prameswari; Mohamad Afrizal (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2026)
This study analyzes the representation of social actors in criminal murder news published on Kompas.com using Theo van Leeuwen’s critical discourse analysis approach. The research aims to identify the strategies of inclusion and exclusion employed by journalists in constructing the positions of perpetrators, victims, witnesses, and legal institutions in online news discourse. This study used a qualitative descriptive method with documentation and note-taking techniques to collect data from eighteen murder-related news articles published on Kompas.com during April–May 2026. Data were analyzed through categorization of discourse representation strategies, including nomination-categorization, objectivity-abstraction, assimilation-individualization, association-dissociation, activation-passivation, determination-indetermination, and personalization-impersonalization. The findings reveal that journalists predominantly use nomination-categorization and objectivity-abstraction strategies to emphasize factual accuracy and maintain journalistic neutrality. Meanwhile, impersonalization and indetermination are frequently applied to protect identity and strengthen institutional objectivity. The discourse construction also reflects ideological tendencies in positioning law enforcement institutions as authoritative actors while victims are often represented through relational and emotional framing. These findings contribute to discourse studies by demonstrating how linguistic structures in online criminal reporting shape public perception of justice, authority, and victimhood in digital journalism.